Exploring the use of social media during the 2014 flood in Malaysia - Tengku Mohd Azzman, Tengku Siti Aisha; Wok, Saodah; A.Manaf, Aini Maznina; Ismail, Rizalawati (Elsevier, 2015)
In December 2014, one of the most perilous floods in recent years occurred in Malaysia, and many lost their lives, material possessions, and even homes. This paper aimed to explore the use of social media for information sharing about the flood. Survey questionnaires were distributed among families in the East Coast of Malaysia that was directly affected by the flood (N = 507). In light of the recent popularity of social media, this paper could shed light on how social media could be utilized to share critical information during disaster periods, where traditional mainstream media, may not be readily available.